Utilization of Picture Story Books to Improve Reading Speed of Second Grade Elementary School Students Through Differentiation Approach - Setiyaningrum, Ayu; Zulaeha, Ida; Haryadi, Haryadi (Universitas Negeri Semarang, 2024)
One of the independent curriculum programs is independent learning. Independent learning means exploring the greatest potential of educators and students to innovate and improve the quality of learning independently. Based on the results of interviews with class II teachers of SDN Tinjomoyo 01, it is known that reading skills in class II are good, only in reading words that they recognize in everyday life fluently still need to be improved. Therefore, this study aims to increase the reading speed of students by utilizing picture story books through a differentiation approach. The method used is the mixed methods method, with a sequential explanatory research design. The techniques used in collecting data include observation, interviews, and documentation. Data analysis uses the reading speed formula, namely the number of words divided by the time taken in one minute. The results of the reading speed of students who have utilized picture story books through a differentiation approach are shown in a recapitulation graph of student reading speed. The average results of student reading speed at the beginning of the study without using picture story books showed a value of 0.922592593. Meanwhile, the average reading speed results of students who have utilized picture story books through the differentiation approach show a value of 1.082592593. Thus, there is an increase of 0.16 for the average reading speed of class II students of SDN Tinjomoyo 01 using picture story books.